Navigating green identity: How SMEs enhance sustainability through social media strategy? - Wangsa, Ignasius Heri Satrya (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This study investigates the role of social media in enhancing SMEs' green organizational identity through the mediating effect of green brand awareness. Drawing on Signaling Theory, we posit that SMEs strategically use social media to communicate their sustainability efforts, thus improving stakeholders' brand awareness and reinforcing internal sustainability commitments. The novelty of this research lies in explicitly examining the combined influence of social media engagement and strategic content planning on green brand awareness and subsequently on SMEs' green organizational identity, a relatively underexplored area within the SME sustainability literature. Data were collected from 100 SME owners in Palembang, South Sumatera, using convenience sampling. The SEM-PLS analysis reveals significant positive effects of engagement and content strategy on green brand awareness. Additionally, green brand awareness significantly mediates the relationships between these social media strategies and SMEs' green organizational identity. However, direct engagement alone was not found to significantly influence green organizational identity. The findings emphasize the critical importance of strategic content planning alongside active engagement to effectively leverage social media for enhancing SMEs' sustainability outcomes. Practical implications include guiding SMEs to adopt integrated social media strategies, thereby strengthening their internal and external sustainability positioning.